Studentsâ Perception on Pre-reading Activities in Basic Reading II Class of the English Language Education Study Program of Sanata Dharma University - Ekaningrum, Vindy Cahya; Prabandari, Carla Sih (LLT Journal: A Journal on Language and Language Teaching, 2015)
The studentsâ perception on the teacher instruction shows whether the teaching techniques meet the studentsâ need or not. Because of this reason, the researcher wants to find out the varieties of pre-reading activities used by the teacher and the studentsâ perception on the implementation of the pre-reading activities. There were two problem formulations in this study: 1) What kinds of pre-reading activities that are used by Basic Reading II teacher in the English Language Education Study Program of Sanata Dharma University? 2) How is the studentsâ perception on pre-reading activities used by the teacher?Â This research was a survey research. In gathering the data, there were two instruments used in this research. They were interview and questionnaire. The interview was done by interviewing the teacher of Basic Reading II Class. The interview was used to answer the first research question about the varieties of pre-reading activities in Basic Reading II class. Then, the researcher distributed the questionnaire to 56 students of Basic Reading II class. The questionnaire was used to answer the second research question about the studentsâ perception on pre-reading activities used by the teacher.Â The result of this research showed that brainstorming, pre-teaching vocabulary, pre-questioning, visual aids, and KWL strategy were the varieties of pre-reading activities used by the teacher. There were two different implementation of pre-teaching vocabulary. There were also two activities combined together, they were the use of visual aids and KWL strategy. The students had positive perception on the implementation of pre-reading activities in Basic Reading II Class.Â DOI: https://doi.org/10.24071/llt.2015.180206